Electrodeposition of Crystalline Gallium‐Doped Germanium and SixGe1−x from an Ionic Liquid at Room Temperature. Issue 4 (29th January 2015) - Lahiri, Abhishek; Olschewski, Mark; Carstens, Timo; El Abedin, Sherif Zein; Endres, Frank
Abstract In this paper, we show the electrodeposition of both gallium‐doped crystalline germanium and SixGe1−x directly on copper at room temperature from an ionic liquid. Germanium and SixGe1−x were electrodeposited on a thin layer of electrodeposited gallium on copper, thereby leading to the formation of crystalline gallium‐doped germanium and SixGe1−x. From the microstructure, it appears that Ge and SixGe1−x dissolve in Ga to form an amalgam, which then recrystallises to form a crystalline structure. X‐ray diffraction confirmed the formation of crystalline phases. The indirect band gap of the gallium‐doped germanium measured by using scanning tunnelling spectroscopy is (0.9±0.1) eV.